Efeito de borda em fragmentos de floresta montana, Nova Friburgo - RJ - Barros, Fabiana Abreu de (2006)
Forest fragmentation has been promoting intense degradation of one of the most threatened biomes: the Atlantic Forest. During human occupation of land, the natural ecosystems were converted in agricultural, grazing, or urban areas, leading to loss of native species, invasion by exotic species, soil erosion and pollution of water bodies. Several aspects have influence in the number of species that are able to survive in a forest remnant, such as size and isolation degree of the remnant, frequency and intensity of anthropogenic disturbance and type of surrounding vegetation. The aim of this work was investigate the effect of surrounding land use on forests remnants through the analysis of floristic composition and vegetation structure in a Montane Forest, Nova Friburgo RJ. The sampling was carried through 12 transects of 50 x 5 m installed in remnants with agricultural and pasture edge, and in the interior of the remnants. In each transect, all individuals with DAP ≥ 5 cm had been sampled, totalizing 721 individuals, belonging to 166 species and 42 families. The species number varied from 62 to 83 species between the plots. The index of diversity for the total area was 4,10 nats/ind, varying from 3,37 to 3,85 nats/ind between the samples. Significant differences between the two types of edge and the interior had been verified for average height, and between the agricultural edge and the interior for average diameter. In the areas of agricultural edge, a significant variation between the bands of distance of the edge and height, as well as for diameter were found. The clusters, structural and floristic analyses has shown a greater variation of the areas of agricultural edge compared with the areas of grass edge and interior of forest, which had presented greater similarity between themselves. The results suggest that remnants with agricultural edge suffer greater influence from the surrounding land use than remnants with grass edge, associated to physical factors as soil type (relief/topography) and to the intrinsic region environmental heterogeneity